Study of blood lead and semen lead concentration in male infertility - Debnath, BC; Ibrahim, M; Fatima, P (Pulse, 2011)
Objective: To evaluate the association of blood and semen lead with male infertility. Design: It was a case control study carried out in the department of Biochemistry, BSMMU, from January, 2004 to December, 2004. Subjects: Of 52 male subjects, 26 were infertile with oligospermia and / or asthenospermia. Age matched 26 normospermic subjects with normal standard semen parameters (volume, count, motility and morphology) were selected as controls. None had the history of occupational exposure to lead. Results: Median values of blood lead were 19.96 µg/dl and 17.68 µg/dl (normal <25 µg/dl); semen lead were 29.56µg/dl and 28.17 µg/dl (normal 15.37 ± 3.92 µg/dl) in cases and controls respectively. Neither blood lead nor semen lead showed significant difference between cases and controls. There was significant positive correlation between blood lead and semen lead concentrations. There was no significant correlation of semen and blood lead concentrations with other semen parameters & serum hormone concentrations (FSH, LH, & Testosterone) in cases. Conclusion: Though the association of blood or semen lead with male infertility was not established in our study, yet, increased seminal lead concentration found in our study subjects may be indicative of subtle exposure of lead in our environment. So, further study with larger sample size is needed. The clinicians should consider the lead measurements when evaluating male partners of couples with unexplained infertility and for assessment of lead status, semen lead measurement can be recommended. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6955 Pulse Vol.4 January 2010 p.10-13